2SPD-041 Drug shortages analysis from an italian hospital pharmacy perspective. (March 2019) - Inserra, C; Zovi, A; Piacenza, M; Zerega, G
Abstract : Background: The Italian market, as well as other markets, is experiencing an increasing frequency of drug shortages, which have caused difficulties for clinicians, healthcare facilities, patients and regulators. Drug shortages can occur for many reasons including manufacturing and quality problems, regulatory issues and business decisions. They adversely affect patient care by causing the substitution of safe and effective therapies with alternative treatments, compromising or delaying medical procedures or causing medication errors. Purpose: The aim of the work is to analyse the drug shortages phenomenon at the centre between January 2016 and June 2018. Material and methods: Every drug included in the hospital formulary from January 2016 to June 2018 was considered for the analysis. Drugs involved in shortages were defined as drugs related to delay in supply and included in the official list of the national regulatory agency. For each drug, data extracted were: information about active ingredient, dosage, pharmaceutical form, drug category, reason for shortage, medication shortage status (solved/unresolved), differences in costs and time to purchase the alternative drug from abroad. Results: Six drugs included in the hospital formulary were involved in drug shortages during the fixed time (0 in 2016; one in 2017; five in the first semester of 2018) including: Benzylpenicillin benzathine 1, 200, 000 UI injection vials (2017), Mupirocin 2% ophthalmic ointment, Ampicillin 1 g oral tablets, Clorfenamin 100 mg injection vials, Alprostadil 600 mg oral tablets and Etilefrin 10 mg injection vials (2018). Drug shortages are still unresolved for Mupirocin, Ampicillin, Clorfenamin and Benzylpenicillin benzathine (66%), while they were solved within 90 days for Alprostadil and Etilefrin (33%). The main drug categories involved in shortages were: antibiotics (50%), urological drugs (16.6%), anti-histamines (16.6%) and adrenergic drugs (16.6%). The reason for shortages were manufacturing problems (five) or temporary marketing discontinuation (one). Costs of purchasing alternative drugs increased by 3.5 times compared to ordinary costs, and the purchasing process took twice as long as it would be ordinarily. Conclusion: According to results, the drug shortages phenomenon is increasing significantly over time, including relevant drugs. As purchasing alternative drugs from abroad was a long and expensive process, drug shortages at the centre also increased the burden on healthcare providers and healthcare facility finances. References and/or acknowledgements: No conflict of interest.